Alien plant species: here to stay? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
In a massive job creation programme in South Africa, 21,000 unemployed people, mostly women, have been employed to tear out harmful invasive plants, including trees (mainly acacia), prickly bushes and cacti, and aquatic plants. These plants, some of...